Establishment of H3K9me3-dependent heterochromatin during embryogenesis in Drosophila miranda - Kevin H-C Wei; Carolus Chan; Doris Bachtrog (eLife, 2021)
Heterochromatin is a key architectural feature of eukaryotic genomes crucial for silencing of repetitive elements. During Drosophila embryonic cellularization, heterochromatin rapidly appears over repetitive sequences, but the molecular details of how heterochromatin is established are poorly understood. Here, we map the genome-wide distribution of H3K9me3-dependent heterochromatin in individual embryos of Drosophila miranda at precisely staged developmental time points. We find that canonical H3K9me3 enrichment is established prior to cellularization and matures into stable and broad heterochromatin domains through development. Intriguingly, initial nucleation sites of H3K9me3 enrichment appear as early as embryonic stage 3 over transposable elements (TEs) and progressively broaden, consistent with spreading to neighboring nucleosomes. The earliest nucleation sites are limited to specific regions of a small number of recently active retrotransposon families and often appear over promoter and 5’ regions of LTR retrotransposons, while late nucleation sites develop broadly across the entirety of most TEs. Interestingly, early nucleating TEs are strongly associated with abundant maternal piRNAs and show early zygotic transcription. These results support a model of piRNA-associated co-transcriptional silencing while also suggesting additional mechanisms for site-restricted H3K9me3 nucleation at TEs in pre-cellular Drosophila embryos.